Webster's New World Dictionary of American English - Chief in Editor Neufeldt, Victoria and Editor in Chief Guralnik, David B. (New Yoek Webster's New World, 1988)
"Nearly 80 million desks and bookshelves worldwide boast a member of the distinguished family of Webster's New World dictionaries. From the New York Times to the Los Angeles Times, most major newspapers have adopted the College Edition as their standard first-reference resource. So have the Associated Press and United Press International. The professionals know that when you need to get the words rights the first
Keywords: English language -- Dictionaries -- Americanisms -- Dictionaries -- Americanisms